Réponses

2014-01-06T15:12:43+01:00
1)
P=(2a+3)²+(3a-5)²
P=4a²+12a+9+9a²-30a+25
P=13a²-18a+34
2)
a) a=2
P=13(2)²-18(2)+34
P=52-36+34=50
b) a=-3/2
P=13(-3/2)²-18(-3/2)+34
P=13(9/4)+54/2+34
P=117/4+54/2+34
P=117/4+108/4+136/4
P=361/4
c) a=0
P=13(0)²-18(0)+34
P=0-0+34=34
2014-01-06T15:36:34+01:00
1) Développer l'expression :
P = (2a + 3)² + (3a - 5)²
P = 4a² + 12a + 9 + 9a² - 30a + 25
P =13a² - 18a + 34

2) Calculer l'expression P pour a = 2, a = -3/2 et a = 0
a) Pour a = 2
P = 13 (2)² - 18 (2) + 34
P = 52 - 36 + 34
P = 50

b) Pour a = -3/2
P = 13 (-3/2)² - 18 (-3/2) + 34
P = 13 (9/4) + 54/2 + 34
P = 117/4 + 54/2 + 34
P = 117/4 + 108/4 + 136/4
P = 361/4

c) Pour a = 0
P = 13 (0)² - 18 (0) + 34
P = 0 - 0 + 34
P = 34